2013
DOI: 10.1007/s00268-013-2020-y
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Lymph Node Dissection in Papillary Thyroid Carcinoma: Is There a Place for Lateral Neck Dissection?

Abstract: In preoperatively N0 PTC patients, LN metastases are frequent in central and ipsilateral lateral compartments. Prophylactic LND in the central and ipsilateral lateral compartments should therefore be recommended in the presence of PTC to identify high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 39 publications
(37 reference statements)
5
41
1
Order By: Relevance
“…However, Ducoudray et al [9] considered that prophylactic CLN and LLN dissection could modify PTC staging and simplify postoperative management for clinicians, so they recommend that selective prophylactic CLN and LLN dissection (ipsilateral to the main tumor) be performed in apparently node-negative PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ducoudray et al [9] considered that prophylactic CLN and LLN dissection could modify PTC staging and simplify postoperative management for clinicians, so they recommend that selective prophylactic CLN and LLN dissection (ipsilateral to the main tumor) be performed in apparently node-negative PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, given the potentially high prevalence of LNM in PTMC, some authors agree that prophylactic lymph node dissection (LND) permits an improved staging of the disease that may guide subsequent treatment;14 however, few studies have demonstrated a meaningful role of prophylactic LND in relation to locoregional control or survival in PTMC. A systematic review that included 8,345 PTMC patients explored the risk factors associated with central lymph node metastasis (CLNM) and proposed that prophylactic central lymph node dissection (CLND) should be considered in PTMC patients with risk factors 15.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid regional recurrence, predictive factors for regional LNM, such as primary tumor size, extracapsular invasion, or maximum Standardized Uptake Value (SUVmax) on PET were vigorously investigated (22), and prophylactic neck dissections were required in some studies (5). In this study, the factors affecting central LNM were age, main tumor size, and the number of retrieved central LNs, according to multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic LNs are hard to cure without surgical removal and any surgical intervention for recurrent LNs increases the risk of surgical complications due to postoperative adhesion. To overcome such challenges, many surgeons perform prophylactic CCND (5). However, unnecessary and excessive prophylactic CCND can also cause adverse events including permanent hypocalcemia or irreversible nerve injury.…”
Section: Introductionmentioning
confidence: 99%